(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The analysis shows a significant similarity in the German people’s idea of the world. This similarity is due to the coincidence of the socio-historical conditions of life of peoples, the general patterns of development of human existence, which provide a common experience, a common knowledge of the “rules of life.” This knowledge has its source not only in the directly acquired experience of generations, but also in the experience enshrined in biblical sayings.